Role of Modified Endoscopic Medial Maxillectomy in Persistent Chronic Maxillary Sinusitis - Thulasidas,Ponnaiah (2014)
Introduction Functional endoscopic sinus surgery has a long-term high rate of success for symptomatic improvement in patients with medically refractory chronic rhinosinusitis. As the popularity of the technique continues to grow, however, so does the population of patients with postsurgical persistent sinus disease, especially in those with a large window for ventilation and drainage. In addition, chronic infections of the sinuses especially fungal sinusitis have a higher incidence of recurrence even though a wide maxillary ostium had been performed earlier. This subset of patients often represents a challenge to the otorhinolaryngologist. Objectives To identify the patients with chronic recalcitrant maxillary sinusitis and devise treatment protocols for this subset of patients. Methods A retrospective review was done of all patients with persistent maxillary sinus disease who had undergone modified endoscopic medial maxillectomy between 2009 and 2012. We studied patient demographics, previous surgical history, and follow-up details and categorized the types of endoscopic medial maxillectomies performed in different disease situations. Results We performed modified endoscopic medial maxillectomies in 37 maxillary sinuses of 24 patients. The average age was 43.83 years. Average follow-up was 14.58 months. All patients had good disease control in postoperative visits with no clinical evidence of recurrences. Conclusion Modified endoscopic medial maxillectomy appears to be an effective surgery for treatment of chronic, recalcitrant maxillary sinusitis.